2011
DOI: 10.1021/ie201610g
|View full text |Cite
|
Sign up to set email alerts
|

Remixing Control for Divided-Wall Columns

Abstract: The divided-wall column is an energy-saving promising technology for the separation of ternary mixtures, but control is difficult because of its complexity structure and interactions of control loops. Although a few control methods have been reported, the general control method for all ternary mixtures is still pending because of the difference of relative volatilities. In this work, we explore a new control structure by control the remixing of the intermediate at the top trays in the prefractionator section f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…3 a shows that the remixing effect appears in column I in the TCS, since the mass fraction of DMF reaches a maximum value at stage 28 but it gradually drops with increasing stage number. In general, the remixing of DMF induces a thermodynamic loss [24]. Fig.…”
Section: Dividing-wall Columnmentioning
confidence: 99%
“…3 a shows that the remixing effect appears in column I in the TCS, since the mass fraction of DMF reaches a maximum value at stage 28 but it gradually drops with increasing stage number. In general, the remixing of DMF induces a thermodynamic loss [24]. Fig.…”
Section: Dividing-wall Columnmentioning
confidence: 99%
“…Design and control are two important engineering aspects of the DWC. Controlling a DWC is more difficult than conventional separation sequences, because of the complex nonlinear interaction between controlled variables and manipulated variables . There are eight manipulated variables in DWC, namely, the heat duty of the condenser ( Q c), distillate flow rate ( D ), bottoms flow rate ( F bot ), side stream flow rate ( S ), reflux flow rate ( L ) or reflux ratio ( RR ), vapour boil‐up ( V ), liquid split ratio ( RL ), and vapour split ratio ( RV ) .…”
Section: Introductionmentioning
confidence: 99%
“…Controlling a DWC is more difficult than conventional separation sequences, because of the complex nonlinear interaction between controlled variables and manipulated variables. [21][22][23][24] There are eight manipulated variables in DWC, namely, the heat duty of the condenser (Qc), distillate flow rate (D), bottoms flow rate (F bot ), side stream flow rate (S), reflux flow rate (L) or reflux ratio (RR), vapour boil-up (V), liquid split ratio (RL), and vapour split ratio (RV). [25] Because the location of the fixed wall determines how the vapour flow splits between the two sides of the column, RV is not considered a manipulated variable in dynamic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have proposed different control structures in the DWC that adequately reject different disturbances obtaining good results: Van Diggelen et al [6] [7] extended the time-optimal control concept to the case of dividing-wall distillation columns, the DWC topology was designed in the frame of HYSYS simulator, a dynamic model was elaborated on the basis of this structure, and the optimal startup time was defined, using iterative dynamic programming as the optimization procedure. Hao Ling et al [8] explored a new control structure by controlling the remixing of the intermediate component at the top stages in the prefractionator section, it was found that avoiding the remixing of the intermediate component helps the DWC work very close to the optimal conditions. Ignat and Woinaroshy [9] studied the controllability of DWCs using a four-point control structure, based on PID loops with inferential temperature measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Three loops aimed to regulate the composition of three product streams, and the fourth control loop aimed to achieve minimum energy operation. [3,5,8,15] In some cases, a trade-off between energy efficiency and controllability have been reported. [15] In this paper, the application of a novel temperaturetemperature cascade control scheme as the fourth control loop for the Petlyuk column is explored.…”
Section: Introductionmentioning
confidence: 99%